Thunderstorm wind load evaluation on storm shelters using wind tunnel testing. (1st July 2022) - Ghazal, Tarek; Aboutabikh, Moustafa; Aboshosha, Haitham; Abdelwahab, Mohamed
Highlights: Three storm shelters were tested experimentally for thunderstorm wind loads. Wind tunnel was used to evaluate the structural and cladding loads. Comparative study between thunderstorm and boundary layer responses was conducted. Response coefficients associated with thunderstorms were suggested. Abstract: In Canada, there is a growing number of thunderstorms capable of generating intensive gust fronts and tornadoes, which drastically affect people living in rural areas. Currently, the influence of windstorms is not sufficiently accounted for in building codes such as the National Building Code of Canada (NBCC 2015). Moreover, people in rural areas are more prone to those weather-related fatalities due to the lack of suitable storm shelters. The current study aims at studying the aerodynamic behavior of storm shelters subjected to non-synoptic wind (i.e., downbursts). Wind tunnel tests were conducted at Ryerson University for the three commonly used storm shelter shapes in Canada for different angles of attack. Mean force and moment coefficients were found and benchmarked against similar data for the same models obtained from a turbulent boundary layer wind tunnel test. Afterwards, the maximum absolute design force and moment coefficients resulting from all angles of attack were identified, and a design example for storm shelters in Canada was given to compare between downburst and boundary layer design loads.